Kalender Jawa Islam Menurut Ronggowasito Dalam Serat Widya Pradhana - Mahmudah, Yumna; Izzuddin, Ahmad (Universitas Islam Negeri Mataram, 2023)
Historians present the origin of the Javanese Islamic calendar by associating it with Sultan Agung, in contrast to the explanation in the fiber Widya Pradhana, Ronggowasito precisely mentions that the Javanese Islamic calendar was formulated by Sunan Giri II. So it can be examined is there a difference between the calculation of the calendar formulated by Sultan Agung and Sunan Giri II as described by Ronggowasito. This study used a qualitative descriptive approach, with secondary data taken from the manuscript fiber Widya Pradhana. The results of the study will be divided into two, the difference in terms of calculation and in terms of the function of the Javanese Islamic calendar in both versions.